Simulation-Based Cost Analysis of Industrial Supply of Chips from Logging Residues and Small-Diameter Trees - Raul Fernandez-Lacruz; Anders Eriksson; Dan Bergström (Forests, 2019)
Research Highlights: The use of terminals can increase supply costs by 5–11% (when compared to direct supply), but terminals help secure supply during peak demand and cope with operational problems in the supply fleet in cases where direct supply chains would be unable to meet demand on time. Background and Objectives: This work analyses the supply cost of chipped logging residues and small-diameter trees, from chipping at roadside storages to delivery to the end-user. Factors considered include demand curves (based on the requirements of a theoretical combined heat and power plant or biorefinery); demand volume; and mode of supply (direct or combined via terminal). The impact of longer trucking distances from the sites, and supply integration between forest and other land (varying relocation distances) was also assessed. Materials and Methods: The operational environment and work of a theoretical chip supplier in northern Sweden were modelled and simulated in ExtendSim®. Results: The mean supply cost of chips was 9% higher on average for combined chains than for direct chains. Given a high demand, 8% of the annual demand could not be delivered on time without using a terminal. High supply integration of forest and other land reduced supply costs by 2%. Contractors’ annual workloads were evened out by direct supply to the biorefinery (which has a relatively steady demand) or supply via-terminal independently of the end-user. Keeping distinct chips from different sites (implying that trucks were not always fully loaded) instead of mixing chips from different sites until the trucks were fully loaded increased supply costs by 12%. Conclusions: Terminals increase supply costs, but can enable demand to be met on time when direct supply chains alone might fail. Integrated supply planning could reduce supply costs by increasing the utilization of residual biomass from other land.